Awake fiberoptic intubation in a pediatric patient with Tessier’s cleft: Navigating the challenges - Jyoti Sharma; Ruhi Sharma; Mohd A. Mir; Anju Grewal (Saudi Journal of Anaesthesia)
Awake fibreoptic intubation is the gold standard of airway management in anticipated difficult airways. Paediatric patients with orofacial defects pose unique challenges to the anaesthetist as management requires meticulous planning and preparation as well as titration of drugs to maintain spontaneous ventilation without losing the airway. We report a case of an 11-year-old patient with Tessier cleft type 4,6 posted for orbital reconstruction and discuss the management with awake fibreoptic intubation.